Sulfonic acid functionalized mesoporous silicas and organosilicas: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Srilakshmi, Ch.; Parischa, Renu; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
Ethane bridged mesoporous organosilicas and MCM-41 having sulfonic acid groups in the pore channels were prepared by co-condensation method as well as grafting method, using 3-mercaptopropyltriethoxysilane (3-MPTS) as the sulfur precursor. TEM and N-2 sorption isotherm analysis revealed that the mesoporous structural ordering is retained after the functionalization and modifications of organic groups while FT-IR, Raman, XPS and solid-state C-13 CP MAS NMR shows the presence of sulfonic acid groups and the stability of the mesoporous framework. The catalytic activity of the developed materials was evaluated in the liquid phase Claisen-Schmidt condensation reaction of acetophenone with benzaldehyde, to probe the effect of mesoporous support surfaces as well as the role of preparation methods. Results showed that sulfonic acid functionalized ethane-silica samples were more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: condensation; ethane-silica; heterogeneity; sulfonic acids

Synthesis of tinidazole by condensation-oxidation sequence using MoO3/SiO2 bifunctional catalyst - Chandorkar, J. G.; Shubhangi B. Umbarkar; Rode, C. V.; Kotwal, V. B.; Dongare, Mohan K. (Catalysis Communications, 2007)
Antimicrobial drug, tinidazole has been synthesized by condensation of 2-methyl,5-nitro-imidazole and 2-ethyl-thio-ethanol over MoO3/SiO2 catalyst to obtain 1-(2-ethyl-thio-ethanol)-2-methyl-5-nitro-imidazole which is further oxidized using hydrogen peroxide using the same MoO3/SiO2 catalyst to obtain tinidazole. MoO3/SiO2 catalyst (20%), synthesized by sol-gel process showed the highest acid strength and was successfully demonstrated to catalyze both condensation and oxidation in the synthesis of tinidazole. Due to the bifunctional activity of the catalyst, the use of acetic acid for condensation step and tungstic acid or ammonium molybdate for oxidation step in the conventional synthesis of tinidazole could be eliminated, thus making it an environmentally benign process. The catalysts could be recycled five times without any appreciable loss in the conversion and selectivity showing the potential for. the use of MoO3/SiO2 as bifunctional catalyst for the production of this industrially important compound. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: antimicrobial drug; condensation; MoO3/SiO2; Oxidation; solid acid catalyst; tinidazole

Synthesis of norpandamarilactonines, pandamarilactonines, and pandanamine - Gogoi, Sanjib; N. P. Argade (Synthesis-Stuttgart, 2008)
A facile route to naturally occurring (+/-)-norpandamarilactonines A and B, (+/-)-pandamarilactonines A-D, and pandanamine has been described from 3-methylfuran-2(5H)-one, with a reductive intramolecular aza-Michael-type addition as the key step.
Keywords: 3-methylfuran-2(5H)-one; condensation; intramolecular aza-Michael reaction; pandamarilactonines

Synthesis and in vitro study of 14-aryl-14H-dibenzo[a.j]xanthenes as cytotoxic agents - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Mujahid, Mohammad; Sehar, Irum; Saxena, Ajit K. (Bioorganic & Medicinal Chemistry Letters, 2009)
A simple and expedient method for the synthesis of a series of 14-aryl-14H-dibenzo[a.j]xanthenes is described through a one-pot condensation of beta-naphthol with aryl aldehydes catalysed by TaCl(5) under solvent-free conventional heating. The major advantages of the present method are: high yields, less reaction time, solvent-free condition and easy purification of the products. The synthesized 14-aryl-14H-dibenzo[a.j]xanthenes were evaluated against a panel of six human cancer lines of different tissues. Synthesized compound 30 showed IC(50) of 37.9 and 41.3 mu M against Colo-205 and 502713, respectively, whereas 3g showed IC(50) of 41.9 mu M against Colo-205. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde; beta-Naphthol; condensation; Cytotoxicity; One-pot reaction; Solvent-free; Tantalum(V) chloride; Xanthenes

Highly selective claisen-schmidt condensation catalyzed by silica chloride under solvent-free reaction conditions - Hazarkhani, Hassan; Kumar, Pradeep; Kondiram, Kadam Sachin; Gadwal, Ikhlas M. Shafi (Synthetic Communications, 2010)
Silica chloride serves as a useful catalyst in the cross-aldol condensation, leading to the synthesis of a wide variety of bisarylidene cycloalkanones and chalcones. The catalyst showed high selectivity; self-condensation of ketones was not observed.
Keywords: Aldol reaction; arylidene cycloalkanone; Claisen-Schmidt; condensation; silica chloride

Synthesis of chenopanone - Deore, Prashant S.; N. P. Argade (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2014)
Starting from glyoxalic acid, a facile three step approach to chenopanone has been described utilizing the Barbier reaction as a key step.
Keywords: acid hydrolysis; Barbier reaction; chenopanone; condensation; Glyoxalic acid; isovaleraldehyde; synthesis

Stereoselective synthesis of subincanadine alkaloids framework - Kalshetti, Manojkumar G.; Argade, Narshinha P. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
Starting from, N-tosyltryptamine and (S)-acetoxysuccinic anhydride, a facile synthesis of (-)-indolizinoindolone has been demonstrated as a basic structural outline of bioactive subincanadine alkaloids. Regioselective Grignard reaction with (S)-acetoxysuccinimide, stereoselective intramolecular cyclization to form (-)-indolizinoindolone skeleton and TiCl4 induced condensation with acetaldehyde for stereoselective generation of exocyclic carbon carbon double bond are the key features.
Keywords: (S)-Acetoxysuccinimide; alane reduction; condensation; Grignard reaction; indolizinoindolone; PCC-oxidation; stereoselective Pictet-Spengler cyclization

Understanding the role of solvent properties on reaction kinetics for synthesis of silica nanoparticles - Bari, Atul H.; Jundale, Rajashri B.; Kulkarni, Amol. A. (Chemical Engineering Journal, 2020)
The effect of various alcoholic solvents and their compositions on the size of silica particles synthesized through hydrolysis and condensation of tetraethyl orthosilicate (TEOS) is studied. The alcohols used are: Methanol, ethanol, propanol, i-propanol, butanol, pentanol, hexanol, octanol, decanol and do-decanol. Ethanol was used as a co-solvent with the higher molecular weight alcohols. Silica particles of size between 100 nm and 2 mu m were obtained by changing solvent composition. Concentrations of total soluble silica and silicic acid were measured and used for exploring the kinetics of hydrolysis and condensation reactions. Polarity, steric hindrance and viscosity of solvent were found to have a strong influence on the rate constants and size of silica nanoparticles. An attempt is made to correlate both final particle size and rate constants with dielectric constant, Wiener index and viscosity of the solvent.
Keywords: condensation; Hydrolysis; kinetics; silica particles; Solvents; Stober process